1 William Waller Hening, The Statutes at Large: Being a Collection of all the Laws of Virginia 226 (1809) - (:unkn) unknown (My University, 1639)
"ALL persons except negroes to be provided with arms and ammunition or be fined at pleasure of the Governor and Council"
Keywords: REQUIRED POSSESSION; ENSLAVED PERSONS AND OTHER MINORITIES